A Multi-Parameter Splitting Extrapolation and a Parallel Algorithm for Elliptic Eigenvalue Problem (Journal of Computational Mathematics, 1998)
The finite element solutions of elliptic eigenvalue equations are shown to have a multi-parameter asymptotic error expansion. Based on this expansion and a splitting extrapolation technique, a parallel algorithm for solving multi-dimensional equations with high order accuracy is developed.
Keywords: Finite element; multi-parameter error expansion; parallel algorithm; splitting extrapolation.